The CALM1 core promoter polymorphism is not associated with hip osteoarthritis in a United Kingdom Caucasian population. - Loughlin, J; Sinsheimer, J; Carr, A; Chapman, K (2006)
OBJECTIVE: A convincing genetic association with hip osteoarthritis (OA) of a functional single nucleotide polymorphism (SNP) in the core promoter of the calmodulin 1 gene CALM1 was recently reported in a Japanese population. The T-allele of the SNP encoded OA susceptibility and this was mediated by a reduced expression of CALM1. Our objective was to assess whether the SNP was also associated with hip OA in UK Caucasians. METHODS: The SNP was genotyped in 920 cases that had undergone elective joint replacement of the hip due to end-stage primary OA and in 752 age-matched controls. RESULTS: Our study had greater than 97% power to observe an effect comparable to that seen in the Japanese study. However, there was no significant difference (P< or =0.05) in genotype or allele frequencies between our cases and our controls. There was also no significant difference when the cases were stratified by sex. CONCLUSION: Our data on a cohort of 1672 individuals implies that the CALM1 core promoter polymorphism is not a risk factor for OA etiology in Caucasians. Our study does not call in to question the veracity of the Japanese report. Instead it highlights the heterogeneous nature of OA genetic susceptibility.